Pelatihan Pemanfaatan Tanaman Obat Keluarga Sebagai Jamu Peningkat Imunitas di Desa Situterate - Fitri, Dewi Rahma; Fajar, In Rahmi Fatria; Hardiyati, Iin; Adiana, Budi; Sihombing, Kartini (Jurnal Abdimas Jatibara, 2023)
The family medicinal plant is a home-cultivated plant that has medicinal properties. One of the uses of TOGA is as a healthy drink and increases immunity. Plants used in immunity-boosting herbs include ginger, turmeric, lemongrass, lemon, cinnamon, fennel, cardamom, and second. The purpose of counseling and training is to increase public knowledge about medicinal plants and using medicinal plants correctly for indications of proper self-medication and how to process herbal medicine. The outreach activity was started by providing material about the benefits of family medicinal plants and continued with training on making immunity-boosting herbs. The results of community service activities in Situterate Village obtained an increase in public understanding of the use of family medicinal plants which was realized by making immunity-enhancing herbs. This knowledge about TOGA becomes the basis for performing self-medication treatment and making various kinds of TOGA-based products appropriately.